Hi-Tech homo: генезис и перспективы - Шелковая, Н. В. (НТУ "ХПИ", 2017)
В статье выявляются особенности современной западной цивилизации, анализируется влияние Hi-Tech на природу человека, выдвигается гипотеза о циклическом характере духовного развития человечества.

The author of the article reveals the peculiarities of modern western civilization, analyzes the influence of Hi-Tech on human nature, suggests a hypothesis about the cyclic character of the spiritual development of mankind.
Hi-Tech homo: genesis and perspectives
Keywords: Интернет; Интернет-зависимость; сетевая культура; коммуникант; виртуальная коммуникация; Hi-Tech; Internet; Internet-addiction; Hi-Tech homo